2002
DOI: 10.1023/a:1021643229028
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have investigated the effect of documented protein palmitoylation inhibitors on the fatty acylation and intracellular transport of myelin proteolipid protein (PLP). To this end, brain slices from 20-day-old rats were incubated with either [3H]palmitate or [3H]leucine in the presence or absence of various concentrations of 2-fluoropalmitate (FP), cerulenin (CER), or tunicamycin (TM). FP (> or = 10 microM) decreased the cellular uptake of [3H]palmitate and consequently reduced the labeling of palmitoyl-CoA, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…These findings suggest that cerulenin has a minimal effect on the incorporation of exogenously added long chain fatty acid into cellular lipids. However, treatment with higher (> 1mM) concentrations of cerulenin result in reduced palmitate incorporation into phosphatidylcholine, but not other phospholipids [30]. No changes in uptake of labeled palmitate or its conversion to palmitoyl CoA were observed with cerulenin.…”
Section: Inhibition Of Protein Palmitoylation Withmentioning
confidence: 85%
See 4 more Smart Citations
“…These findings suggest that cerulenin has a minimal effect on the incorporation of exogenously added long chain fatty acid into cellular lipids. However, treatment with higher (> 1mM) concentrations of cerulenin result in reduced palmitate incorporation into phosphatidylcholine, but not other phospholipids [30]. No changes in uptake of labeled palmitate or its conversion to palmitoyl CoA were observed with cerulenin.…”
Section: Inhibition Of Protein Palmitoylation Withmentioning
confidence: 85%
“…A recent study with a related halogen substituted palmitate analog, 2-fluoropalmitate, concluded that this compound inhibited uptake of [3H] palmitate into brain cells, perhaps by competing with palmitate for cellular entry. As a result, 2-fluoropalmitate treatment leads to decreases in [ 3 H]palmitoyl CoA levels and decreased fatty acylation of phospholipids and myelin proteolipid protein [30].…”
Section: Inhibition Of Protein Palmitoylation With 2-bromopalmitate (mentioning
confidence: 99%
See 3 more Smart Citations